Persepsi Tentang Tugas dan Motivasi Kerja Serta Pengaruhnya terhadap Kinerja Guru BK SMPN se-Kota Kupang - Wens Nagul; A Muri Yusuf; Syahniar Syahniar (Jurnal Konseling dan Pendidikan, 2013)
This study is setting of issues about how the perception of task and work motivation influencing much on the performance of BK teacher/counselor at Junior High Schools in Kupang city. The goal is to describe the influence of perception on task and work motivation of BK teacher/counselor in the performance of duties in the school. The research uses a quantitative approach with descriptive methods. The results of this study showed that the perception of task and work motivation of BK teacher/counselor give a very significant influence on the performance of BK teachers/counselor in execution of duty.